Photophysical and dielectric properties of nanostructured epoxy thermosets containing poly(N-vinylcarbazole) nanophases. (19th August 2016) - Xiang, Yixin; Li, Lei; Zheng, Sixun
Abstract: In this contribution, we reported the preparation of the nanostructured epoxy thermosets containing poly( N -vinylcarbazole) (PVK) microdomains. Toward this end, we first synthesized poly( N -vinylpyrrolidone)- block -poly( N -vinylcarbazole)- block -poly( N -vinyl pyrrolidone) (PVPy- b -PVK- b -PVPy) triblock copolymer via sequential reversible addition-fragmentation chain transfer/macromolecular design via the interchange of xanthate (RAFT/MADIX) process; then this triblock copolymer was incorporated into epoxy to obtain the nanostructured thermosets. It was found that reaction-induced microphase separation occurred in the mixtures of this triblock copolymer with epoxy. The formation of the PVK microdomains in epoxy thermosets were investigated by means of transmission electron microscopy (TEM) and small angle X-ray scattering (SAXS). Owing to the creation of PVK nanophases, the nanostructured epoxy thermosets became light-emissive under ultraviolet irradiation. The photoluminescent behavior is attributable to the formation of the excimers within the PVK microdomains. Compared to control epoxy, the nanostructured thermosets significantly displayed the enhanced dielectric constants due to the formation of PVK nanophases. The enhanced dielectric constants resulted from the dominant contribution of electron polarization and interfacial polarization with the formation of PVK nanophases. Graphical abstract: Highlights: PVPy- b -PVK- b -PVPy triblock copolymer was synthesized via RAFT polymerization. This copolymer was in cooperated into epoxy to obtain the nanostructured thermosets. The thermosets displayed photoluminescent behavior and enhanced dielectric constant.